Development of a High-Throughput Screen for Inhibitors of Epstein-Barr Virus EBNA1 - Thompson, Scott (2010)
Latent infection with Epstein-Barr Virus (EBV) is a carcinogenic cofactor in several lymphoid and epithelial cell malignancies. At present, there are no small molecule inhibitors that specifically target EBV latent infection or latency-associated oncoproteins. EBNA1 is an EBV-encoded sequence-specific DNA-binding protein that is consistently expressed in EBV-associated tumors and required for stable maintenance of the viral genome in proliferating cells. EBNA1 is also thought to provide cell survival function in latently infected cells. In this work we describe the development of a biochemical high-throughput screening (HTS) method using a homogenous fluorescence polarization (FP) assay monitoring EBNA1 binding to its cognate DNA binding site. An FP-based counterscreen was developed using another EBV-encoded DNA binding protein, Zta, and its cognate DNA binding site. We demonstrate that EBNA1 binding to a fluorescent labeled DNA probe provides a robust assay with a Z-factor consistently greater than 0.6. A pilot screen of a small molecule library of ~14,000 compounds identified 3 structurally related molecules that selectively inhibit EBNA1, but not Zta. All three compounds had activity in a cell-based assay specific for the disruption of EBNA1 transcription repression function. One of the compounds was effective in reducing EBV genome copy number in Raji Burkitt lymphoma cells. These experiments provide a proof-of-concept that small molecule inhibitors of EBNA1 can be identified by biochemical high-throughput screening of compound libraries. Further screening in conjunction with medicinal chemistry optimization may provide a selective inhibitor of EBNA1 and EBV latent infection.